Performance Development of Phra Nakorn Khiri Muang Phet Fair - Winothaka, Theewara; Boonpeng, Suphannee (Journal of Humanities and Social Sciences Review, 2023)
This study is qualitative research. The objective of this study was to study the development of performing arts at the Phra Nakhon Khiri - Muang Petch Fair. The scope of the study was from 1986 to 2020. The methodology of this study was learning, searching, and collecting data from the documents, interviews, and participant and non-participant observations to analyze and summarize the data. The results found that performances at the Phra Nakorn Khiri Fair have been continuously adjusted and developed. However, they adhered to the performance of local arts and culture. The performance styles in the Phra Nakorn Khiri Fair were: 1) standard performances; 2) folk performances; 3) creative performances; and 4) musical performances. The performances would be set at various locations within the Phra Nakhon Khiri Fair. The development of performances was divided into three periods, depending on the agencies working on performance management and the social situation in each year. During the first period of 1986-2005, it was found that the performances were mainly in the form of folk performances. The second period, 2006-2014, began with educational institutions playing a role in the management of performances, of which the teachers were coordinators. During the third period, 2015-2020, the field in front of Phra Nakhon Khiri was renovated into a park in honor of His Majesty King Mongkut. Therefore, the performances were set in this area. This research is considered to disseminate local arts and culture and promote tourism in Phetchaburi Province. It is also useful to those who are interested in studying further.